Can Brain Natriuretic Peptides and Osteoprotegerin Serve As Biochemical Markers for the Detection of Aortic Pathology in Children and Adolescents with Turner Syndrome? - Mavinkurve, Meenal; O’Gorman, Clodagh S. (Frontiers in Endocrinology, 2017)
Turner syndrome (TS) is a chromosomal disorder that affects 1:2000 females. It results from either the complete or partial loss of the X chromosome as well as other aberrations. Clinical features of TS include short stature, delayed puberty, and congenital cardiac malformations. TS children also have an increased prevalence of cardiometabolic risk factors which predisposes them to complications like coronary artery disease , cardiovascular related deaths and aortic dissection. Early cardiac imaging, such as echocardiography and cardiac magnetic resonance imaging, are recommended to detect underlying aortic pathology. However, these modalities are limited by cost, accessibility and are operator dependent. In view of these shortcomings, alternative methods, like vascular biomarkers are currently being explored. There are only a few studies which have examine the relationship between BNP, NT pro-BNP and OPG and aortic disease in TS and thus the data is only in proof of concept stages. Further meticulous longitudinal studies are required before BNP, NT pro-BNP and OPG are used as vascular biomarkers for the detection of aortic disease in childhood and adolescent TS.